Rootstocks for Florida Peaches, Nectarines, and Plums - James Ferguson; Jose Chaparro (EDIS)
HS-1110, a 5-page illustrated fact sheet by J. Ferguson and J. Chaparro, provides commercial nurseries and growers information about 'Flordaguard' rootstock, other rootstocks no longer recommended for Florida stone fruit and procedures for harvesting, cleaning, and stratifying 'Flordaguard' seed prior to planting. Published by the UF Department of Horticultural Sciences, October 2007.